2018
DOI: 10.1002/cbdv.201800230
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Geographical Mapping of Essential Oil Volatiles in Heracleum (Apiaceae): Identification of Novel Compounds and Unraveling Cryptic Variation

Abstract: Conspecific populations of plants in their native range are expected to show considerable variation due to long-term ecological and evolutionary factors. We investigated the levels of secondary metabolites in Heracleum including H. persicum a valuable medicinal plant to depict the magnitude of cryptic variation and the potential significance of novel chemical traits. The essential oil volatiles from fruits of 34 populations from different species of Heracleum in Iranian distribution range and a native of H. sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…In Flora Iranica the presence of abaxial leaf trichome is listed as a diagnostic criteria in the latter species [14]. However, other molecular data from these species, including an ITS and trnL-trnF nucleotide analysis, together with a volatile oil composition study, also confirm our observed pattern which suggests a lack of differentiation amongst H. persicum and H. rechingeri populations [4,6,12], and perhaps that the abaxial leaf trichome is an unreliable trait in resolving H. rechingeri and H. persicum. Since inter-specific hybridization has been reported to be prevalent in Heracleum [2,3], the observed patterns can also be interpreted as a lack of fixed differentiation resulting from an introgression of alleles between the congeneric species.…”
Section: Taxonomic Application Of Microsatellite Markerssupporting
confidence: 74%
See 4 more Smart Citations
“…In Flora Iranica the presence of abaxial leaf trichome is listed as a diagnostic criteria in the latter species [14]. However, other molecular data from these species, including an ITS and trnL-trnF nucleotide analysis, together with a volatile oil composition study, also confirm our observed pattern which suggests a lack of differentiation amongst H. persicum and H. rechingeri populations [4,6,12], and perhaps that the abaxial leaf trichome is an unreliable trait in resolving H. rechingeri and H. persicum. Since inter-specific hybridization has been reported to be prevalent in Heracleum [2,3], the observed patterns can also be interpreted as a lack of fixed differentiation resulting from an introgression of alleles between the congeneric species.…”
Section: Taxonomic Application Of Microsatellite Markerssupporting
confidence: 74%
“…In addition, the three populations from H. pastinacifolium are not genetically differentiated from populations of a morphologically similar species, H. anisactis and H. transcacasicum. Similar studies using ITS and rpl32-trnL nucleotide sequences, or from the analysis of the chemical constituents of essential oils derived from the fruits, have also delimited the thin-and thick stem species, even though H. pastinacifolium and H. anisactis remain similar [4,12]. Limited numbers of cross-amplified microsatellite markers in H. lasiopetalum reveal a distant relatedness of this species within Heracleum.…”
Section: Plos Onementioning
confidence: 94%
See 3 more Smart Citations